COMPREHENSION OF LINKED LIST DIAGRAMS: THE EFFECTS ON CODE WRITING SKILLS - Obaidellah, Unaizah; Md Sabri, Aznul Qalid; Mohd Faizal, Erma Rahayu; Chiam, Yin Kia (Malaysian Journal of Computer Science, 2021)
The use of graphics has a tendency to aid reasoning in program solving by improving novice programmers’ ability to read and write code. This study extends existing work in computer programming on the use of diagrammatic representation for students undertaking the fundamental data structure course (CS2) in Malaysia. Students were tested on comprehension of diagrams followed by the composition of code with respect to the linked list topic. The data was assessed using the inter-rater agreement test and showed a high degree of consistent ratings. Results showed a moderate correlation between students’ ability to analyze list operations in the form of notation and performance on code writing. Students assessed the diagrams differently according to the complexity level. The result can be generalized to conclude that the use of diagrams alone may not fully support reasoning and program solving. However, some types of diagrams are potentially more effective to support code composition and more emphasis should be given to evaluating the effectiveness of diagrams in organizing cues to facilitate novice programmers in program solving. Further investigation on a combination of activities related to comprehension of diagrams, including code reading and explanation prior to code writing, is recommended.